SOCIAL CLASS IN SHORT STORY "HARAPAN DI KOTA KECIL" BY MUSHLIH KHALWANI BASED ON KARL MARX PERSPECTIVE - Ramadhan, Muhammad Labib Bara; Basid, Abdul; Fatim, Al Lastu Nurul (Annual International Conferences on Language, Literature, and Media, 2023)
This study aims to provide new insights to researchers about the phenomenon of social class that exists in literary work in the form of short stories. In addition, this research also aims theoretically to show the conditions of social class, the causes of social class, and the impact of the occurrence of social class in Mushlih Khalwani's short story entitled "Harapan di Kota Kecil" as well as a complement to previous studies on the topic of discussing social class in literary works. This research is a descriptive qualitative research. Descriptive qualitative research describes all types of sign systems that allow a more complete and comprehensive understanding of the subject under study. Defines qualitative research as scientific research aimed at understanding phenomena in a natural social context by prioritizing in-depth communicative interaction between the researcher and the phenomenon under investigation. The upper social class group is evidenced by (1) a group of thugs who acted arbitrarily toward the city residents and (2) the city government who closed their eyes and ears in the case of the death of the owner of the orphanage foundation because they had an interest. (3) Thugs ordered the orphanage children to pickpocket. (4) The court gave the land rights of the orphanage to the government. In addition to the upper-class groups, researchers also found the existence of lower-class groups in the short story "Harapan di Kota Kecil" by Mushlih Khalwani, as evidenced by: (1) city residents who are no longer able to follow the demands of the thugs, (2) the background of the main character in the short story which comes from the laborers and coolies, (3) the owner of the inheritance rights of the foundation's land who lost in court.